Arab Americans’ Perceptions of Police Post 9/11 in Metropolitan Milwaukee - Ayman A. Khatib (Adult Education Research Conference, 2014)
Arab Americans as individuals tend to avoid any contact with the police because many Arabs shun from contacting police that may lead to community marginalization and alienation. The current literature fails to examine in-depth Arab Americans’ perceptions towards police. The literature typically reflects how police officers view Arab Americans but it is silent regarding how Arab Americans view American police.